Automação como suporte à otimização do uso de água e energia na cultura do coco irrigado no município de Neópolis-SE - Carvalho, Hércules Benzota de (2011)
Irrigated agriculture is responsible for the consumption of 70% of all fresh water on the planet. There is, therefore, a necessity of using this scarce and of vital importance resource more rationally. Irrigated agriculture, as well as other activities in rural areas, needs to follow the technological advances. In the last decades, the electronic devices and the computers have got an increasing technological advance, becoming cheaper, precise and with a better user interface. The programmable logic controller is a quite spread use device, and may be used to control irrigation, to command solenoid valves, to switch on pumps, besides storing data; all this through external communication ports. The great advantage of using the programmable logic controller is the customization of activities, that is, the user can elaborate a control logic that suits his/her specific needs. The advantages of an automatic equipment in relation to the human operator are generally: assiduity, speed, precision and cost; its disadvantage is the incapacity to react to disturbances and accidents, apart from those ones predicted in its project. One way to get efficient irrigation and maximize production involves the system automation to determine when and how much to irrigate, through the use of sensor technologies, communication, data processing and acting devices. This work had as main objective the definition and installation of automatic equipments for irrigation control in order to compare the existing methodology, based on automatic temporizing (timer), with the use of sensory automatic and evapotranspiration calculation, thus making possible to analyze the use of water and energy in the process. This study used as an experimental area the green dwarfed coconut irrigated cultivation in HDantas farm in the municipality of Neópolis-SE. As methodology, the PLC man-machine interface was installed and the elaboration of programming logic routines for irrigation control was made, using information from agrometeorological stations and calculation of evapotranspiration. Existing information from the flow meters and the power meter was also used to measure the values of current consumption of water and energy, respectively. The results gotten during the tests showed the reliability of the programmable logic controller use in the execution of control logic and in the irrigation performance, being enough for that the information availability of soil and climate variables relevant to the control method defined in its programming logic.